The true costs of food production in Viet Nam - Benfica, Rui; Davis, Kristin E.; Dao, The Anh; Vu, Dang Toan; Naziri, Diego (International Food Policy Research Institute, 2024)
Key takeaways True cost accounting allows for the measurement of hidden impacts of food production on the environment, human health, and society. • Our findings show that at the national level for all crop sectors: o Environmental externalities account for 73% and social for 27% of external cost structure. o Major environmental impact sources are land occupation, air pollution, and climate change. o Major social impact sources are underpayment of farm workers and the incidence of child labor. • In NATURE+ sites in Sa Pa and Mai Son districts for the crop sector: o External costs represent about 24% of all household crop production costs. o Environmental externalities (61%) are greater than social (39%). o Land occupation is the most important external impact source, followed by soil degradation and climate change. o Under earning (underpayment of workers and/or low famer profits) are significant social costs, followed by the gender wage gap and the incidence of child labor.